Diachronic Changes in German Phonetics: Hänsel und Gretel Movies 1954 vs. 2012 - Sinyaeva Anastasiya Vital'evna; Smirnova Anna Gennad'evna (Виртуальная коммуникация и социальные сети)
Although the German film discourse is a popular research topic, it is seldom considered from the point of view of diachronic phonetics. This research featured the phonetic changes that occurred in the German language in a time span of more than half a century. The German language saw some significant phonetic changes between 1954 and 2012. These changes were reflected in audiovisual discourse. The author applied the notions of orthoepic norm, intonation, and articulatory tension to two film versions of the famous German fairy tale about Hänsel and Gretel released in 1954 (Walter Jansen) and 2012 (Uwe Janson). The research revealed some differences in pronunciation and intonation. However, it was the intonation pattern that changed most dramatically between 1954 and 2012. In the modern film, the speech sounds smoother but less clear and assertive than in the old version.